POSSIBILITIES OF USING E-LEARNING IN TRAINING AND DEVELOPMENT OF EMPLOYEES - Ganieva Dilnoza Baxriddin qizi (Journal of Artificial Intelligence and Digital Economy, 2024)
In the digital age, organizations are increasingly adopting innovative methods to train and develop their employees. E-learning, or electronic learning, has emerged as a key tool in this area, offering flexibility, cost efficiency, and a wide range of interactive content. This scientific article explores the possibilities of using e-learning in the training and development of employees, discussing its benefits, implementation strategies, and potential challenges. The article also provides insights into how e-learning can be effectively integrated into corporate training programs to enhance employee skills and organizational performance.